2016
DOI: 10.1088/1361-648x/aa4e04
|View full text |Cite
|
Sign up to set email alerts
|

The role of sample height in the stacking diagram of colloidal mixtures under gravity

Abstract: Bulk phase separation is responsible for the occurrence of stacks of different layers in sedimentation of colloidal mixtures. A recently proposed theory (de las Heras and Schmidt 2013 Soft Matter 9 8636) establishes a unique connection between the bulk phase behaviour and sedimentation-diffusion-equilibrium. The theory constructs a stacking diagram of all possible sequences of stacks under gravity in the limit of very high (infinite) sample heights. Here, we study the stacking diagrams of colloidal mixtures at… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 35 publications
1
22
0
Order By: Relevance
“…From the bulk phase diagram we construct the stacking diagram by finding the boundaries between two stacking sequences in the stacking diagram. There exist three types of boundaries formed by three sets of special sedimentation paths 41 , Fig. 1 Model.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…From the bulk phase diagram we construct the stacking diagram by finding the boundaries between two stacking sequences in the stacking diagram. There exist three types of boundaries formed by three sets of special sedimentation paths 41 , Fig. 1 Model.…”
Section: Resultsmentioning
confidence: 99%
“…As discussed above, it is useful to group the stacking sequences in a finite height stacking diagram 41 . Figure 4 shows the stacking diagrams for samples with heights h = 5 mm (c,d) and 18 mm (e,f) in the plane of average chemical potentials (c,e) and average packing fractions (d,f) along the path.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The idea is to control the branching rate, since two-patch colloidal particles only form chains and colloidal particles with more patches promote branching. A study based on local density approximation of multilayer stacking of this type of binary mixtures in a gravitational field has shown stacking diagrams with different stacking sequences [72]. The authors studied the effect of the finite thickness of the stacked film on the occurrence of stacks of different layers during sedimentation.…”
Section: Interfacial Propertiesmentioning
confidence: 99%
“…The percolation is only recovered for very high packing fractions. Previous studies of functionalized colloidal particles have reported also reentrant phenomena driven by, e.g., gravitational fields [33,34], competition between different energy scales [35][36][37], and patches activated by temperature [38].…”
Section: Discussionmentioning
confidence: 99%